Efektifitas Pendidikan Kesehatan Penyakit Menular Menggunakan Audio Visual Di MTs Minhajul Ulum Ketara - Diny Aprianti Putri; Fibi Dian Murdianti; Indah Miastuti; Nining Fatria Ningsih (Jurnal Pengabdian Masyarakat: Pemberdayaan, Inovasi dan Perubahan, 2025)
Sexually Transmitted Infections (STIs) and Human Immunodeficiency Virus (HIV) remain significant public health concerns, particularly among adolescents who are vulnerable to misconceptions and misinformation. This study aimed to evaluate the effectiveness of audiovisual media in improving adolescents’ knowledge of STIs and HIV at MTs Minhajul Ulum Ketara, Dusun Dayen Rurung, Desa Ketara. A quasi-experimental design with pre-test and post-test assessments was conducted on 30 male and female students. Participants received an intervention using educational videos from the local health center covering the definition of STIs, examples of diseases, transmission routes, prevention, and healthy behaviors, followed by interactive discussions. Initial results indicated low baseline knowledge, particularly regarding STI prevention, HIV transmission among adolescents, and examples of STIs, with some students still believing myths, such as HIV transmission through shared eating utensils. After the intervention, all indicators showed significant improvement, with the highest increases in STI prevention knowledge (112%), adolescent HIV transmission (106%), and examples of STIs (94%). The effectiveness of audiovisual media was also demonstrated by a 73% increase in the understanding of the media itself. In conclusion, the use of audiovisual media in reproductive health education effectively enhances adolescents’ understanding of STIs and HIV, fosters preventive awareness, and facilitates the internalization of scientific information. This strategy is recommended for sustained implementation as part of adolescent health education programs in schools or madrasahABSTRAKInfeksi Menular Seksual (IMS) dan Human Immunodeficiency Virus (HIV) tetap menjadi masalah kesehatan masyarakat yang signifikan, khususnya di kalangan remaja, yang rentan terhadap miskonsepsi dan informasi keliru. Penelitian ini bertujuan mengevaluasi efektivitas media audio visual dalam meningkatkan pengetahuan remaja tentang IMS dan HIV di MTs Minhajul Ulum Ketara, Dusun Dayen Rurung, Desa Ketara. Metode yang digunakan adalah PkM edukasi partisipatif berbasis evaluasi pada 30 siswa putra dan putri. Peserta menerima intervensi berupa video edukasi Puskesmas yang membahas definisi IMS, contoh penyakit, jalur penularan, pencegahan, serta perilaku hidup sehat remaja, diikuti dengan diskusi interaktif. Hasil kegiatan menunjukkan bahwa edukasi kesehatan menggunakan media audiovisual secara signifikan meningkatkan pengetahuan siswa MTs Minhajul Ulum Ketara tentang IMS dan HIV, dengan perubahan tingkat pemahaman dari kategori rendah–sedang pada pre-test menjadi tinggi pada post-test, terutama pada aspek pencegahan dan klarifikasi miskonsepsi. Kesimpulannya, Media audiovisual terbukti efektif sebagai metode edukasi kesehatan remaja di madrasah karena mampu meningkatkan pengetahuan siswa secara signifikan.